Pengaruh Model Project Based Learning (PJBL)Terhadap Hasil Belajar IPAS Siswa Kelas IV SD Inpres 1 Tumaratas - Posumah, Putri Wulan Teresa; Rorimpandey, Widdy H.F.; Merentek, Risal M. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of the Project Based Learning (PjBL) model on the science learning outcomes of class IV students at SD Inpres 1 Tumaratas. Researchers chose the Project Based Learning (PjBL) model. In this research, researchers used an experimental type of research using a One Group Pretest - Posttest Design research design. Researchers used non-probability sampling methods with saturated sampling techniques to determine the research sample. This research used all fourth grade students at SD Inpres 1 Tumaratas as the research sample. The data collection technique used is a test technique using pretest and posttest. The research results show that the Project Based Learning (PjBL) model has a positive effect on the science and science learning outcomes of class IV students at SD Inpres 1 Tumaratas. This can be proven from the results of the hypothesis test that has been carried out, it is obtained that is 29.275 and is 1.699, so it is obtained that > or 29.275 > 1.699, then is rejected and is accepted, so the hypothesis in this research is accepted. Apart from that, when observations are made, students become more active and more enthusiastic in the learning process using the Project Based Learning (PjBL) model compared to the teaching and learning process that does not use the Project Based Learning (PjBL) model